Interview: Herbal medicine in Botucatu: a history woven by four hands - Leite, Ana Luiza Mamede [UNESP]; Doneida, Victor Carlos (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
In this interview, Stéfano Fais Dematte Gomes and the doctors Karina Pavão Patrício and Augusto Cesar Menezes talk about how they have been working towards the implementation of phytotherapy in Botucatu/SP and the need for networking.
Entrevista: A fitoterapia em Botucatu: uma história tecida por muitas mãos
Keywords: Health System; Herbal medicine; Medicinal plants